1999
DOI: 10.1074/jbc.274.42.29655
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Metallothionein Gene Transcription

Abstract: Metallothioneins are small, cysteine-rich proteins that function in metal detoxification and homeostasis. Metallothionein transcription is controlled by cell-specific factors, as well as developmentally modulated and metal-responsive pathways. By using the nematode Caenorhabditis elegans as a model system, the mechanism that controls cell-specific metallothionein transcription in vivo was investigated. The inducible expression of the C. elegans metallothionein genes, mtl-1 and mtl-2, occurs exclusively in inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 89 publications
4
31
0
Order By: Relevance
“…In the human ␤-globin locus control region, the NF-E2 and GATA transcription factors, when bound to their respective regulatory elements, control the position-independent expression of ␤-globin genes (16,32). In C. elegans the GATA transcription factor (ELT-2) constitutively activates the metallothionein gene expression by binding specific GATA elements, whereas a second metal-responsive factor prevents transcription in the absence of metals (28). Our results constitute the second report that GATA elements regulate HSP70 genes, the first being the description of their role in the regulation of the HSP70 gene of chronic myelogenous leukemia cells (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the human ␤-globin locus control region, the NF-E2 and GATA transcription factors, when bound to their respective regulatory elements, control the position-independent expression of ␤-globin genes (16,32). In C. elegans the GATA transcription factor (ELT-2) constitutively activates the metallothionein gene expression by binding specific GATA elements, whereas a second metal-responsive factor prevents transcription in the absence of metals (28). Our results constitute the second report that GATA elements regulate HSP70 genes, the first being the description of their role in the regulation of the HSP70 gene of chronic myelogenous leukemia cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…We found that in addition to having a strictly regulated pattern of activation, it possesses a promoter region containing two conventional HSEs and an unexpected cluster of GATA motifs. GATA motifs have already been described in stress gene promoters, for example, in the Caenorhabditis elegans metallothionein genes mtl-1 and mtl-2 (28) and in the T. thermophila metallothionein gene MTT1 (10); however, these GATA motifs have never been shown to interact with the heat shock response machinery.…”
mentioning
confidence: 99%
“…Binz and Kagi (1999) did not allocate annelid MTs to a family. Metallothionein genes are organized as multigene families displaying developmentally regulated expression patterns, as well as cell-type-specific regulation (Jahroudi et al 1990;Freedman et al 1993;Moilanen et al 1999). Expression of MT is controlled mainly at the transcriptional level by several agents, including metals, hormones, UV irradiation, and free radicals (Imbert et al 1990;Thiele 1992;Andrews 2000).…”
Section: Principal Characteristics Of Mts and Their Biological Rolesmentioning
confidence: 99%
“…The transcription of these genes is induced by cadmium exposure and other stresses that do not involve metals, but not by high levels of zinc exposure. Loss-of-function mutants of mtl-1 and mtl-2 display enhanced cadmium toxicity, but a role in zinc metabolism has not been detected (Freedman et al 1993;Moilanen et al 1999;Swain et al 2004). Phytochelatins are peptides that can bind metals and contribute to cadmium tolerance.…”
mentioning
confidence: 99%